Kvantifikace rizik pro úrazové pojištění - Jindrová, Pavla; Kopecká, Lucie (Univerzita Pardubice, 2017)
People of all ages are threatened by accident. They have not many options of protection against financial impacts that are caused by accident. Accident insurance is often taking out insurance in the insurance practice. This article is focusing on quantification of risks for accident insurance. There are described possibilities of measuring risks and using of suitable models. There are modelled number and amount of insurance benefit using real data of the Slovak insurance companies. The data of the Slovak insurance companies is selected specifically for the case of death due to accident. Data contain information about the number of insured persons and number of insured events. The insurance companies cannot estimate premium separately for men and women due to EU Regulation. In this article, firstly, the premium is estimated separately for men and women and secondly this estimation is designed for both sexes. There is shown decision of EU affect amount of premium.
Quantification of risks for accident insurance
Keywords: risk; quantification; binomial/beta model; Bayesian estimation; maximum likelihood estimation; C11; C13; G22